Lower charge, higher order: Revising electrostatic control of nematic phases in 2D polyelectrolytes - Mohsen Moazzami Gudarzi; Mohamad Ali Sanjari Shahrezaei; Seyed Hamed Aboutalebi (Proceedings of the National Academy of Sciences, 2026)
Classical theories of nematic ordering in charged platelets predict that increasing surface charge stabilizes alignment. They also predict enhanced alignment when ionic strength is reduced. Here, in agreement with established theories, we show that in graphene oxide (GO) and related two-dimensional polyelectrolytes, nematic order and structural color emerge as surface charge density is reduced, concomitant with a decrease in self-generated ionic strength and an increase in the effective range of electrostatic repulsion. Using a minimal model combining counterion-only Poisson–Boltzmann electrostatics, van der Waals attraction, and Helfrich undulation, we show that ordering is governed by a self-screened electrostatic length scale, d EDL , set by particle-released counterions. When d EDL scale becomes comparable to the interlayer spacing, spacing fluctuations are suppressed and long-range orientational order is enhanced. Our results provide a general framework for controlling structure and optics in 2D polyelectrolyte assemblies.